2006
DOI: 10.1002/chem.200600462
|View full text |Cite
|
Sign up to set email alerts
|

Apoptolidin A: Total Synthesis and Partially Glycosylated Analogues

Abstract: The total synthesis of apoptolidin A is described employing an early glycosylation strategy. Strategic disconnections were chosen between C11-C12 (cross-coupling) and C19O-C1 (macrocyclization). The cis-selective glycosylation at C9-OH was achieved with the new SIBA protective group at O2/O3 of the L-glucose residue. Auxiliary substitutents at the 2-position of the 2-deoxy sugars were applied to form selectively the glycosidic linkages of the C27 disaccharide. The cross-coupling of the glycosylated northern ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…[1,2] Carbohydrate-derived acetals substituted with PhS groups undergo highly diastereoselective reactions, and substrates of this type have been applied in natural product synthesis, [3] as illustrated in Scheme 1. [4] Similar observations have been made in glycosylation reactions of furanose derivatives (Scheme 2). [5] Other substituents, such as PhSe groups [6,7] and halogens (particularly I [8][9][10][11] ), have also been employed.…”
Section: Introductionsupporting
confidence: 61%
“…[1,2] Carbohydrate-derived acetals substituted with PhS groups undergo highly diastereoselective reactions, and substrates of this type have been applied in natural product synthesis, [3] as illustrated in Scheme 1. [4] Similar observations have been made in glycosylation reactions of furanose derivatives (Scheme 2). [5] Other substituents, such as PhSe groups [6,7] and halogens (particularly I [8][9][10][11] ), have also been employed.…”
Section: Introductionsupporting
confidence: 61%
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 94%
“…Successful total synthesis of 1 has been achieved by the groups of Nicolaou [138][139][140] and Koert [141,142]. Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142].…”
Section: Methodsmentioning
confidence: 99%
“…26 2,6-Anhydro-5-deoxy-1,3-O-(di-tert-butylsilanylidene)-D-arabino-hex-5-enitol (503 mg, 1.76 mmol) was then dissolved in acetone (4L/mol) under inert atmosphere (N 2 ) and the mixture was cooled down Zinc bromide lithium bromide solution in n-dibutyl ether. Inside a glovebox, a 50 mL Schlenk tube with magnetic stirrer was charged with solid zinc bromide (7.11 g, 31.6mmol), lithium bromide (2.74 g, 31.6mmol) and n-dibutyl ether (30 mL).…”
Section: 6-anhydro-5-deoxy-13-o-(di-tert-butylsilanylidene)-4-o-(2mentioning
confidence: 99%